Cultural Capacity of Polewali Mandar Youths: A Case Study on Language and Art Performance - Rabiatul Adawiah (Program Studi Pendidikan Bahasa Inggris FKIP Universitas Muslim Maros, 2023)
Youths are the next generation and the heirs to local culture. This study aims to investigate the knowledge and cultural capacity of the youth in the Polewali Mandar regency, specifically related to their local language and arts. To obtain data, researchers use the survey method with the help of Google Forms. The participants in this study were 80 people with 5 representatives from each sub-district in the region. The results showed that there are 61.25% of young people still use Mandarese at home. Meanwhile, in offices, schools, and markets, only about 42-25% speak the local language. Furthermore, the capacity of youth in the local arts is also still very low. On average, their ability to perform Kalindaqdaq, kacaping, and traditional dances is only around 33%. Based on the results of this research, it is necessary to make efforts to maintain and involve youth in each of these efforts.